Pemberdayaan Masyarakat sebagai Upaya Pengendalian Hipertensi melalui Gerakan Edukasi dan Pemanfaatan Inovasi Bunga Telang (GEMILANG) - Aini Syarah Ramadhani; Shalwa Fitra Ramadhina; Vivianita Anggun Lestari; Nenih Nurhasanah; Fitriani Sri Rahayu; Nabila Asyifa; Syalsabila Pulungan; Syifa Aulia Puspita; Ultanika Indraswarni Anwar; Muhammad Fathan Mubina Tsaubudin; Ninda Salma Nurfitri; Raysha Chaidar; Neni Neni (STIKES Columbia Asia Medan, 2025)
Hypertension is a non-communicable disease with an increasing prevalence and is a major risk factor for cardiovascular diseases. In Cikabuyutan Timur, Hegarsari Subdistrict, hypertension is a significant health problem, primarily caused by unhealthy dietary habits. As a community-based effort to control hypertension, the GEMILANG (Educational Movement and Utilization of Butterfly Pea Innovation) program was implemented through a community empowerment approach. This program includes hypertension education, training on processing butterfly pea flowers into herbal tea, and a Training of Trainer (ToT) for the Kelompok Wanita Tani (KWT) on butterfly pea cultivation techniques. The evaluation results from pre-test and post-test assessments indicated an increase in participants’ understanding of hypertension and the benefits of butterfly pea flowers, with the average pre-test score rising from 83.33 to 93.89 in the post-test. The Wilcoxon test showed a significant difference between pre-test and post-test results (p-value = 0.007). This program successfully enhanced community knowledge and skills in managing hypertension naturally. It is expected that this initiative will be sustainable through the active involvement of KWT and health cadres in promoting a healthy lifestyle based on herbal plants.